Video project in distance learning during the pandemic: Readiness, processes, and benefits - Abdul Rasid Saraha; St. Hayatun Nur Abu; Fitriyana Ibrahim; Nurfatimah Sugrah; Khusna Arif Rakhman (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
Research on video-making on project-based distance learning (VPjDL) was conducted for prospective chemistry teacher students to solve the problem in an educational system due to the Coviv-19 pandemic. In this study, a questionnaire analysis was conducted on the readiness of resources, the learning process and student motivation in distance learning based on video-making projects. In contrast, learning outcomes are measured based on aspects of creative thinking skills. This study aimed to determine the relationship between resource readiness, learning process, and motivation for distance learning based on video-making projects on creative thinking skills. The relationship between resource readiness, learning process and motivation on VPjDL is the novelty of this article. In this study, the number of samples used was 30 students. Data analysis was performed using the Pearson Bivariate correlation. The data analysis results show a relationship between resource readiness, learning process, and motivation to students' creative thinking skills. On the other hand, student creativity is shown by video products with a very high level of originality.